A customised safety assurance assessment model for a liquefied natural gas tanker - Manivannan Subramaniam, 1969-; Ab. Saman Abd. Kader; Fakulti Kejuruteraan Mekanikal (2012)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2012